2021
DOI: 10.1016/j.xfre.2021.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported menstrual and obstetric outcomes following hysteroscopic adhesiolysis for Asherman syndrome

Abstract: Objective: Review the menstrual and obstetric outcomes among Asherman syndrome patients when stratified by disease severity. Design: Retrospective cohort study. Setting: A community teaching hospital affiliated with a large academic medical center. Patients: A total of 355 Asherman syndrome patients stratified by March classification who underwent hysteroscopic adhesiolysis. Interventions: Telephone survey, analyzed with multivariable analysis. Main Outcome Measures: Return of menstruation. Pregnancy, miscarri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Several published reports claimed that the purported similarity between syncytin-1 and the SARS-CoV-2 spike protein may induce immune cross-reactivity resulting in female sterility [ 10 , 11 ]. Morris used frozen embryo transfer as a model for comparing the implantation rates between SARS-CoV-2 vaccine seropositive, infection seropositive, and seronegative women [ 5 ]. No difference was found in serum beta hCG documented implantation rates or sustained implantation rates between the three groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several published reports claimed that the purported similarity between syncytin-1 and the SARS-CoV-2 spike protein may induce immune cross-reactivity resulting in female sterility [ 10 , 11 ]. Morris used frozen embryo transfer as a model for comparing the implantation rates between SARS-CoV-2 vaccine seropositive, infection seropositive, and seronegative women [ 5 ]. No difference was found in serum beta hCG documented implantation rates or sustained implantation rates between the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…No difference was found in serum beta hCG documented implantation rates or sustained implantation rates between the three groups. The author concluded that reports claiming that COVID-19 vaccines or illness cause female sterility are unfounded [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intrauterine adhesion (IUA) was first proposed by Heinrich Fritsch in 1894 ( 1 ), and Joseph G Asher-Man published a series of papers in 1948 to name the disease and describing it in detail, so it is also called Asherman syndrome ( 2 ). IUA is a common intrauterine disease, referring to adhesion or even occlusion of uterine isthmus and cervical canal caused by various reasons ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%